2020
DOI: 10.3389/fmars.2020.00430
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Northwest Pacific Fishery Stocks Using Two New Methods: The Monte Carlo Catch-MSY (CMSY) and the Bayesian Schaefer Model (BSM)

Abstract: The CMSY and Bayesian Schaefer model (BSM) methods were applied to assess datalimited fishery stocks in the Japan Sea and surrounding areas of the Northwest Pacific. Ten stocks including 4 fish species and 5 cephalopod species were assessed; the CMSY method was used in 3 stocks with catch data only, and the BSM method in 7 stocks with both catch time series and catch per unit effort (CPUE) data available. The two methods estimated the maximum intrinsic rate of population increase (r) and carrying capacity of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Similarly, Ji et al (2019) found a good match between the estimates of population parameters of Trichiurus lepturus in the Yellow and Bohai Seas obtained by using CMSY and those from the Schaefer and Fox models. Thus, the CMSY method can for assessing data-limited fisheries, although the related BSM methods, which additional information (e.g., CPUE data) produces narrower confidence intervals (Ren and Liu, 2020). The intrinsic rate of population growth (r) is key in defining the response of populations to challenges such as fisheries (Cheung et al, 2005;Anderson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ji et al (2019) found a good match between the estimates of population parameters of Trichiurus lepturus in the Yellow and Bohai Seas obtained by using CMSY and those from the Schaefer and Fox models. Thus, the CMSY method can for assessing data-limited fisheries, although the related BSM methods, which additional information (e.g., CPUE data) produces narrower confidence intervals (Ren and Liu, 2020). The intrinsic rate of population growth (r) is key in defining the response of populations to challenges such as fisheries (Cheung et al, 2005;Anderson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In general, caution must be exercised when assessing the stock status using this method (Dowling et al, 2019). However, the papers in SMFEA, including those by Liang et al (2020), Ren and Liu (2020), Wang et al (2020a), Zhang et al (2020), and WA2020, have all applied CMSY to assess the stock status, without discussing the potential bias. A discussion related to bias based on previous studies is thus necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term trends in fisheries production in Japan peaked in the late 1980s and then declined sharply with the collapse of Japanese sardine (Tian et al, 2006;Ren and Liu, 2020). The reason was mainly due to heavy fishing, followed by the effect of the reduction in seawater temperature during this period (Tian et al, 2006).…”
Section: Discussionmentioning
confidence: 99%